IMPROVING THE GROWTH AND PRODUCTIVITY OF FIG TREES BY SPRAYING WITH MORINGA LEAVES EXTRACTS AND GARLIC CLOVES - Sara K. H. Taha; Ali M. A. O. Aljabary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This experiment was conducted in a private orchard at Aldaraman, Kirkuk Governorate on "Khalobaziani" local fig trees. This study aimed to investigate the effect of spraying with Moringa leaf extract (MLE) at (0, 2, and 4 ml.l-1) and Garlic cloves extract (GCE) at (0, 10, and 20 ml.l-1) on growth and productivity of fig trees. Results showed that trees sprayed with MLE 4 ml.l-1 led to a significant increase in the leaf area, total chlorophyll content, average leaf dry weight, minerals (NPK) content in leaves, average fruit weight and size, and average yield per tree, while significantly decreased fruit cracking percentage compared to control. Furthermore, significant increase in the leaf area, total chlorophyll content, average leaf dry weight, minerals (NPK) content in leaves, and average fruit weight and size in the trees sprayed with GCE 20 ml.l-1 compared to control. The interaction between MLE 4 ml.l-1 and GCE 20 ml.l-1 showed a significant increase in the leaf area, total chlorophyll content, average leaf dry weight, and minerals (NPK) content in leaves, also significantly decreased fruit cracking percentage compared to most of the other treatments.